Students' belief towards COVID-19 vaccine: a challenge in reopening university / Nor Azimah Abd Aziz - Abd Aziz, Nor Azimah; Masuri, Mohammad Ghazali; Danis, Ajau; Isa, Siti Nor Ismalina; Illia, Kartini; Loganathan, Mathumalar; Md Isa, Khairil Anuar (Faculty of Health Sciences, Universiti Teknologi MARA, 2023)
Little is known about health sciences students' belief and its relation to COVID-19 vaccine uptake as vaccination program was already taken place in Malaysia. An anonymous electronic survey of health sciences students was conducted at one large Malaysian university setting. The objectives of this study were the students' beliefs and actual behaviour towards Covid-19 vaccines. Students' beliefs about COVID-19 vaccines were elicited through a series of questions about the vaccine's acceptance, the risk of COVID -19 exposure, the perceived severity of COVID -19 and their negative attitudes towards vaccination. The main outcome of the study was the students' acceptance of COVID-19 vaccines and multiple logistics regression was performed to elucidate associated factors related to COVID-19 vaccine acceptance. A total of 275 students participated in this survey. The average age of the participants was 21.9(0.9) and more than three quarters of them (82.5%) were female. Most of the respondents have completed the COVID -19 booster vaccination (82.9%), and a higher acceptance of the vaccine 4.8 (95% CI: 4.7- 4.8). Students' risk of COVID-19 exposure, perceived severity of COVID -19 and their negative attitudes towards vaccination were measured at 0.4 (95% CI:0.3-0.5), 3.8(95% CI: 3.7-4.0) and 3.2 (95% CI: 3.1-3.2) respectively. Student belief in the safety of the COVID-19 vaccine was the only significant factor in vaccine acceptance. While health sciences students reported having high acceptance and vaccine uptake, concerns about the safety of the vaccine safety remained.